Quoting Speech in Early English - Moore, Colette (New York : Cambridge University Press, 2011)
"Before quotation marks became widespread convention, English texts were organized more fluidly, employing varying lexical and textual strategies for marking represented discourse. When we add our present-day quotation marks to editions of Middle English texts, we also overlay our modern interpretation of speech representation, with its expectations of faithful reporting and carefully delineated voices. In doing so, we mask the less-determined nature of early speech marking, and obscure the ways that its plasticity functions as a narrative and stylistic tool. This book provides the first full study of speech representation in pre-modern English. Studying the pragmatic and discourse strategies of English texts from 1350-1600 is essential to reading Middle English works and to understanding the cultural assumptions implicit in the production of early written texts"--
Machine generated contents note: Introduction; 1. Methods of marking speech; 2. Interpreting reported speech: defamation depositions, sermons, chronicles; 3. Reported speech in literary texts: stylistic implications; Conclusion: pragmatic palimpsests; Appendices; Works cited; Index.
Includes bibliographical references and index.
Keywords: Quotation; English language -- Discourse analysis; English language -- Middle English, 1100-1500 -- Terms and phrases; Grammar, Comparative and general -- Interrogative; LANGUAGE ARTS & DISCIPLINES / Linguistics / Historical & Comparative